A Review of Green Public Procurement in the EU - Karnabos, Dimitris; Mitoula, Roido; Tragaki, Alexandra; Apostolopoulos, Constantinos (European Journal of Applied Sciences, 2022)
Public authorities are major consumers in Europe. Each year they spend approximately 2 trillion euros, equivalent to some 19% of the EU’s Gross Domestic Product on the purchase of goods, such as office equipment, building components and transport vehicles; services, such as buildings maintenance, transport services, cleaning and catering services and works. By promoting and using "Green Public Procurement (GPP)" public authorities can drive the market to greener products and services, achieving an important reduction of the environmental impacts. Within the EU public procurement is subject to a number of sources of Community law. In addition, there are common criteria for the adoption of Green Public Procurement in specific sectors (i.e. copying and graphic paper, office IT equipment, cleaning products and services, transport, construction, etc.) and a number of sources of interpretation of the relevant laws and principles (i.e. the "Buying Green handbook"). On the review of GPP the work team firstly analyzed the EU strategic policy, and then chose a series of examples to evaluate the implementation of GPP, illustrate how public authorities have made greener purchasing a reality and provide guidance to others. The evaluation included some of the most interesting case studies related to different countries (i.e. Netherlands, Denmark, Sweden, Malta, Austria, Belgium, Spain, Switzerland, Slovenia, Bulgaria, Latvia, France, UK, Germany, Greece, Finland, etc.) and collected by European Commission over the years. According to the results of the evaluation the benefits associated with GPP are not limited only to environmental impact, but can include everything from social and health to economic and political benefits. Today even if the concept of GPP has been widely recognised as a useful tool, it remains a voluntary instrument. Member States should be encouraged to draw up Action Plans for greening their public procurement. Among other, the coming years should be a growing political commitment at national, EU and international level.